Development of robotic system to enhance therapeutic gastrointestinal (GI) endoscopic procedures - Phee, Louis Soo Jay. (2009)
In line with minimally invasive surgery (MIS), flexible endoscopy is used to inspect and treat disorders of the gastrointestinal (GI) tract without the need for creating an artificial opening on the patient‟s body. The endoscope is introduced via the mouth or anus into the upper or lower GI tracts respectively. A miniature camera at the distal end captures images of the GI wall that help the clinician in his/her diagnosis of the GI diseases. Simple surgical procedures (like polypectomy and biopsy) can be performed by introducing a flexible tool via a working channel to reach the site of interest at the distal end. The types of procedures that can be performed in this manner are limited by the lack of maneuverability of the tool. More technically demanding surgical procedures like hemostasis for arterial bleeding, suturing to mend a perforation, fundoplication for gastrooesophageal reflux cannot be effectively achieved with flexible endoscopy. These procedures are often presently being performed under opened or laparoscopic surgeries. With the invention of medical robots like the Zeus [1] and Da Vinci [2] surgical systems, clinicians are now able to maneuver surgical tools accurately and easily within the human body. Operating from a master console, the clinician is able to control the movements of laparoscopic surgical tools real time. These tools (also known as the slaves) are designed with sufficient degrees of freedom to move according to the natural hand and wrist motion allowing the clinician to perform intricate procedures with minimal technical difficulties. The authors strongly believe that the same concept could be applied to flexible endoscopy as well, yielding the following advantages: -Enables endoscopists to perform more difficult surgical procedures otherwise reserved for opened or laparoscopic surgeries. -Ergonomically designed system reduces technical requirements of the endoscopist yet enhancing his/her surgical capabilities. -Patients need only undergo day surgeries for procedures that would currently require major surgeries. -Less pain and trauma for patients. -Costs and hospitalization stays would be reduced dramatically. The robotic system would work in tandem with current flexible endoscopes.